Penyuluhan Hukum Pencegahan Penyalahgunaan Narkoba di Desa Ciomas, Ciawigebang - Teti Mardiani; Sarip Hidayat; Iman Jalaludin Rifai; Muhammad Beben Bahtiar; Dikri Alpan Fadilah; Dila Nabila; Feby Adzkari; Muhamad Alfi; Suwari Akhmaddhian (Empowerment : Jurnal Pengabdian Masyarakat, 2025)
Narcotics, Psychotropics and addictive drugs commonly called DRUGS are the types of drugs/substances needed in the world of medicine. However, if it is used without careful restrictions and supervision, it can cause dependence and can endanger the health and even the soul of the wearer. Drug abuse is a crime against humanity and an acute social problem that destroys the foundations of social, national and state life. The steps for carrying out legal counseling activities are carried out in three stages. First, the preparation stage looks at the conditions in the field regarding the Dangers of Drug Abuse. Second, the implementation stage of community service is by conducting outreach to the community about the regulations governing drug abuse and providing an understanding of the dangers of drug abuse. Third, it is the implementation stage where the knowledge gained from this socialization can be applied. Implementation of Legal Counseling activities for the Ciomas Village community to increase public knowledge about the Dangers of Drug Abuse. The event was held in Ciomas Village, Ciawigebang District, Kuningan Regency, to be precise at the Multipurpose Building in Ciomas Village. This event was opened with remarks from the Lecturer of the Faculty of Law, University of Kuningan to convey the intent and purpose of holding this event and was followed by remarks from the head of Ciomas Village as a welcome greeting. This event was well received by the Ciomas village community, who attended in total of 30 people divided from several hamlets in Ciomas village. The benefit of holding legal counseling in Ciomas Village, Ciawigebang District, Kuningan Regency, West Java Province is to create better community legal awareness so that each member the community is aware of and lives up to their rights and obligations as citizens and creates a legal culture in attitudes and behavior that is aware, obedient and obedient to the law and can understand the impact of the Danger of Drug Abuse.